Do convencional ao agroecológico: a trajetória do agricultor de Santa Maria de Jetibá - ES - Lemos, Maria Isabel Louzada (2021)
This work aims to analyze the development of agroecology based on the municipality of Santa Maria de Jetibá, Espírito Santo, due to its pioneering nature in these practices in the state, under the hypothesis that the use of agroecological practices is beneficial in Brazil and in world, given the environmental and social damage caused by the conventional farming system. To this end, several currents of alternative agriculture were initially analyzed and how agroecology fits into this spectrum, together with its cultural, anthropological aspects and its contribution to sustainable development. Subsequently, issues related to the municipality of Santa Maria de Jetibá were analyzed, going through its historical formation process, the development of alternative agriculture in the municipality and how they are today. The methods used include a literature review, along with the application of semi-structured changes with farmers in the region, which leads to the identification of gaps such as little technical assistance and funding, difficulty in accessing information and the need for awareness among the population. It is thus concluded that ecologically-based practices can advance in the municipality in question and in the state, so that their commercialization is carried out beyond the municipalities close to the capital, and that this expansion can be enhanced with the help of targeted government policies and change eating habits and consumption of the population in general.